New insights into metabolic dysfunction-associated steatotic liver disease and oxidative balance score - Peng, Lei; Li, Lurong; Liu, Jiahao; Li, Yuanyuan (Frontiers in Nutrition, 2024)
The relationship between oxidative stress and metabolic dysfunctionassociated steatotic liver disease(MASLD) hasn't been studied, which remains inadequately recognized. This is a cross-sectional study in a US adult population to explore the relationship between MASLD and oxidative balance scores(OBS), which containing integrating dietary nutrition and lifestyle factors.We analyzed data from National Health and Nutrition Examination Survey during 2017 to 2018. Multivariate logistic regression, restricted cubic spline curve (RCS) and subgroup analysis were used to investigate the association between OBS and MASLD. Cox regression analysis was utilized to assess the association between OBS and all-cause mortality among individuals.The multivariable-adjusted odds ratio (OR) and 95% confidence interval (CI) for the highest quartile of OBS (Q4) was 0.30 (0.12, 0.77) (P = 0.012) compared to the lowest quartile of OBS (Q1). The RCS regression and subgroup analysis indicated an inverted relationship between OBS and the development of MASLD. The OBS Q4 group (HR: 0.15, 95% CI: 0.03-0.87; p =0.035) exhibited a lower risk of all-cause death than the Q1 group.Conclusions: OBS is statistically significantly and negatively correlated with the risk of MASLD and all-cause mortality in US adults. More prospective investigations are required to substantiate our findings.